Relationship between spiritual intelligence and intolerance of uncertainty, anxiety and fear of Corona in the elderly - Ahmad Maghool; Mahmoud Bakhshi; Sedigheh Rastaghi; Mostafa Rad (Wolters Kluwer Medknow Publications, 2023)
INTRODUCTION: The COVID-19 pandemic has caused physical and psychological health problems in the elderly. Spiritual intelligence has an effect on health and healing. The aim of this study determining the relationship between spiritual intelligence and intolerance of uncertainty, anxiety, and fear of corona in the elderly. METHODOLOGY: A cross-sectional study was done on 207 elderly people who referred to comprehensive health service centers in Mashhad in 2022. The samples were selected based on the inclusion criteria using multistage and cluster sampling. To collect data, various questionnaires were used, including demographic characteristics (age, gender, marital status ...), King's Spiritual Intelligence Questionnaire, Freestone's Intolerance of Uncertainty Questionnaire, Corona Anxiety Scale, and Coronavirus Fear Scale. Statistical analysis of variables was done using descriptive and analytical (independent t-test, Mann-Whitney, analysis of variance, linear regression) tests by means of STATA version 14. RESULTS: The average level of spiritual intelligence was 54.1. Participants reported a high level of intolerance of uncertainty (M = 79.2) and fear of corona (M = 14.09). Education, economic status, and marital status were the predictors of spiritual intelligence of the studied subjects (r = 0.24, P < .05). Spiritual intelligence and gender were also related to uncertainty intolerance (r = 0.12, P < .05). Another finding of the study was the superiority of variables of spiritual intelligence and gender in predicting the level of anxiety of corona compared to other variables (r = 0.17, P < .05). CONCLUSION: There was a relationship between spiritual intelligence, education, and gender with the level of fear and anxiety of corona. Therefore, planning and implementing educational projects based on increasing spiritual intelligence for the elderly with priority for elderly women and with a low level of literacy and income is recommended.